Comparing rates and characteristics of emergency department presentations related to pharmaceutical opioid poisoning in Australia: a study protocol for a retrospective observational study - Dan I Lubman; Suzanne Nielsen; Tina Lam; Janneke Berecki-Gisolf; Jane Hayman; Paul Sanfilippo (BMJ Open)
Introduction and aims Pharmaceutical opioids are an important contributor to the global ‘opioid crisis’, and are implicated in 70% of Australia’s opioid-related mortality. However, there have been few studies which consider the relative contribution of different pharmaceutical opioids to harm.We aim to compare commonly used pharmaceutical opioids in terms of (1) rates of harm, and (2) demographic and clinical characteristics associated with that harm.Method and analysis Observational study of emergency department presentations for non-fatal poisoning related to pharmaceutical opioid use. Data from 2009 to 2019 will be extracted from the Victorian Emergency Minimum Dataset which contains data from public hospitals with dedicated emergency departments in Victoria, Australia’s second most populous state. A combination of free-text and International Classification of Diseases 10th Revision codes will be used to identify relevant cases, with manual screening of each case to confirm relevance. We will calculate supply-adjusted rates of presentations using Poisson regression for all pharmaceutical opioid cases identified, separately for nine commonly prescribed pharmaceutical opioids (buprenorphine, codeine, fentanyl, methadone, morphine, oxycodone, oxycodone-naloxone, tapentadol, tramadol), and for a multiple opioid category. We will use multinomial logistic regression to compare demographic and clinical characteristics, such as triage category, across opioid types.Ethics and dissemination This work is conducted under approval 21427 from the Monash University Human Research Ethics Committee for ongoing injury surveillance. As per conditions of approval, cells of <5 will not be reported, though zeroes will be preserved. We will present project findings in a peer-reviewed journal article as well as at relevant scientific conferences.